Serum levels of cathepsin D, sirtuin1, and endothelial nitric oxide synthase are correlatively reduced in elderly healthy people - Zhong, Yuan; Chen, Alex. F.; Zhao, Jian; Gu, Ying-Jia; Fu, Guo-Xiang (Aging clinical and experimental research, 2016)
Aim Nowadays, cathepsins have been reported to be related to aging. The aim of this study is to evaluate the association between serum levels of cathepsin D (CTSD) and human aging. Methods In the present study, we analyzed the serum levels of CTSD and its relation with levels of sirtuin1 (SIRT1) and endothelial nitric oxide synthase (eNOS) activity, which were known having an important role in aging. This study recruited 90 healthy subjects (62 men and 28 women), which were subdivided into three groups with respect to age: young (about 19 years old, n = 30), middle-age (about 40 years old, n = 30), and aged (above 65 years old, n = 30). Altered serum levels of CTSD and SIRT1 were measured by enzyme-linked immunosorbent assay, and eNOS activity was assessed by the conversion of 14 C - l -arginine to 14 C -L-citrulline. Results Elderly subjects had significantly lower CTSD, SIRT1, and eNOS than younger ones. Serum levels of CTSD were negatively correlated with age. There was a statistically significant positive correlation between serum levels of CTSD, eNOS, and SIRT1. Conclusions This study shows lower serum CTSD values in elderly subjects than in younger subjects. This is the first to demonstrate age-related changes in cathepsin D levels in humans and the association between SIRT1 and eNOS.